Analysis Of Head Nurse’s Leadership Style In Pediatric's Care Ward, Jakarta General Hospital - Andi Amalia Wildani; Cicilia Ika Wulandari (Universitas Respati Yogyakarta, 2020)
The leadership style of a nurse manager has an important role in determining the performance of her staff. An effective leader can bring success in achieving the vision and mission of the hospital. The field study of leadership style in the hospital is one of the efforts to find an overview of the application of effective leadership styles. The method used was literature study which was supported by the results of visit; data collection was carried out usinginterview techniques and observation of leadership style. The results of the field study showed that there were still nurses who were not committed to the team, high workloads and head nurse’s span of control. Thus, the head nurse is required to use a combination of democratic and authoritarian leadership styles to overcome weaknesses and threats that occur in the ward.